2022
DOI: 10.3389/fonc.2022.904790
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies in cervical malignancy-related HPV

Abstract: Despite many efforts to treat HPV infection, cervical cancer survival is still poor for several reasons, including resistance to chemotherapy and relapse. Numerous treatments such as surgery, radiation therapy, immune cell-based therapies, siRNA combined with various drugs, and immunotherapy are being studied and performed to provide the best treatment. Depending on the stage and size of the tumor, methods such as radical hysterectomy, pelvic lymphadenectomy, or chemotherapy can be utilized to treat cervical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 150 publications
0
4
0
1
Order By: Relevance
“…A imunoterapia estimula o sistema imunológico do paciente a reconhecer e combater as células tumorais de forma mais eficaz (KOURY et al, 2018). Essas terapias mais recentes buscam minimizar efeitos adversos e oferecer uma abordagem mais específica contra o câncer cervical, seja de forma individual ou como terapia combinada (AGHBASH et al, 2022). Nesse sentido, as vacinas terapêuticas representam uma estratégia promissora em imunoterapia (LIU et al, 2022).…”
Section: Resultsunclassified
“…A imunoterapia estimula o sistema imunológico do paciente a reconhecer e combater as células tumorais de forma mais eficaz (KOURY et al, 2018). Essas terapias mais recentes buscam minimizar efeitos adversos e oferecer uma abordagem mais específica contra o câncer cervical, seja de forma individual ou como terapia combinada (AGHBASH et al, 2022). Nesse sentido, as vacinas terapêuticas representam uma estratégia promissora em imunoterapia (LIU et al, 2022).…”
Section: Resultsunclassified
“…However, the sample size was small (n = 24; cervical = 19; vaginal/vulvar = 5) and more justifications are needed. Cemiplimab, another anti-PD-1 monoclonal antibody approved to treat squa-mous cell carcinoma in lung and skin cancers [150], was also shown to have preliminary clinical activity in recurrent CC. Cemiplimab and chemotherapy were compared in the international multicentre, randomised, phase III trial GOG-3016 (NCT03257267), which included 608 patients (304 in each arm) and ran between 2017 and 2020.…”
Section: Cervical Cancermentioning
confidence: 99%
“…Nivolumab, pembrolizumab, and atezolizumab are monoclonal antibodies that target the PD-1/PD-L1 and CTLA-4 pathways as immunotherapy (fda. gov) [169,171]. It's worth noting that PD-1/PD-L1 immunotherapy antibodies are related to higher numbers of tumor-infiltrating T CD8+ cells, reinvigorate anti-tumor immunity, and improve patient outcomes [172,173].…”
Section: Human Papillomavirusesmentioning
confidence: 99%
“…Wnt/β-catenin signaling pathway leads to ICI resistance therapy In recent years, treating various solid tumors, such as lung cancer, kidney cancer, and cervical malignancy, through the inhibition of immune checkpoints PD-1/PD-L1 has achieved significant results [171,193]. However, it has been reported that the response to anti-PD-1/PD-L1 monotherapy depends on the extent of tumor-infiltrating lymphocytes [194].…”
Section: Human Papillomavirusesmentioning
confidence: 99%
See 1 more Smart Citation